Trends in behavioral and biological risk factors for non-communicable diseases among adults in Bhutan: results from cross-sectional surveys in 2007, 2014, and 2019 - Pengpid, Supa; Peltzer, Karl (Frontiers in Public Health, 2023)
Background: The study aimed to evaluate trends in the prevalence and correlates of risk factors for non-communicable diseases (NCDs) (low physical activity, insufficient fruit/vegetable intake, current tobacco use, problem alcohol use, diabetes, hypertension, increased total cholesterol and obesity) in Bhutan. Methods: Three repeat cross-sectional Bhutan STEPS surveys (N=9,281) in 2007, 2014 and 2019 were analysed. Results: The proportion of people having 3-8 NCD risk factors significantly decreased from 62.8% in 2007 to 32.6% in 2019 (p<0.001), and the mean number of NCD risk factors significantly decreased from 3.0 in 2007 to 2.1 in 2019 (p<0.001). In linear regression analyses by study year, older age (p<0.001) was across all study years positively associated with eight NCD risk factors. Furthermore, in 2007, male sex (p<0.01) was negatively and in 2019 (p<0.001) was positively associated with eight NCD risk factors. Higher education levels (p<0.05) were in 2007 positively and in 2019 (p<0.05) negatively associated with eight NCD risk factors. Employment (p<0.001) and urban residence (p<0.001) were positively associated in 2019 with eight risk factors for NCD, urban residence (p<0.001) was negatively associated in 2014 with eight NCD risk factors. Conclusion: The prevalence of eight risk factors for NCD decreased in the past 13 years in Bhutan. Inadequate fruit and vegetable intake, problem alcohol use, and hypertension increased, current tobacco use, low physical activity, obesity, diabetes, and raised total cholesterol decreased from 2007 to 2019. Several associated variables were identified for eight and each individual NCD risk factor that can help in guiding interventions.